If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8k + -4k + -8 = 0 Reorder the terms: -8 + 8k + -4k = 0 Combine like terms: 8k + -4k = 4k -8 + 4k = 0 Solving -8 + 4k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 4k = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 4k = 0 + 8 4k = 0 + 8 Combine like terms: 0 + 8 = 8 4k = 8 Divide each side by '4'. k = 2 Simplifying k = 2
| (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x | | .8(x+4)-.3x=1.7 | | n*2-12=34 | | 3y-6y^2=0 | | 25=-7(x+5)+5x | | 5x+8y=6e | | 3x+5=350 | | 8=-4x+x+8 | | ln*(x+3)+ln*9=1 | | 8(x+9)=80 | | (-34)+50+50= | | 85-3x=4 | | -5n=13-13m | | 6x-2y=4x+6y | | y=2x^2-7x-30 | | 8x^2=4x+14 | | 6a+12=6a-12 | | p=8p+p | | -2y=14x-50 | | 12x+8-3x=-1 | | b-8+2b=24 | | 5x-14=-24 |